Implementasi Algoritma K-Means Dalam Mengindentifikasi Kematangan Buah Jambu Madu - Nurdiansyah, Ali; Al-Arrafi, Muhammad Ikhsan; Ramadhanu, Agung (LPPM STIKOM Tunas Bangsa, 2024)
Honey guava is one of the varieties of water guava that has the sweetest taste. This advantage makes honey guava have the potential to be quite popular in several regions in Indonesia and has many enthusiasts to consume honey guava because consuming honey guava can increase skin moisture. The potential of honey guava makes farmers deliberately cultivate honey guava. This study utilizes digital image processing to create a system that can identify the ripeness of honey guava fruit based on RGB (Red, Green, Blue) and HSV (Hue, Saturation, Value) colors. The image in the form of a photo of honey guava fruit taken with a digital camera is processed using MATLAB software and then analyzed using the K-Means Clustering classification method to obtain a comparison of RGB and HSV feature extraction results.